Investment in resilient food systems in the most vulnerable and fragile regions is critical - Queiroz, C.; Norström, Albert V.; Downing, A.; Harmackova, Z. V.; Coning, C. de; Adams, V.; Bakarr, M.; Baedeker, T.; Chitate, A.; Gaffney, O.; Gordon, L.; Hainzelin, E.; et al. (Springer, 2021)
Reversing the alarming trend of rising food insecurity requires transformations towards just, sustainable and healthy food systems with an explicit focus on the most vulnerable and fragile regions.